IMPLEMENTASI KOMPETENSI INTI SEBAGAI PEMBENTUK SEKOLAH BERDAYA SAING DALAM MENANGANI KENAKALAN REMAJA PADA SEKOLAH MENENGAH DESA KASSI LOE DI KABUPATEN PANGKEP - Suwandaru, Rachman; Salam, Karta Negara; Daga, Rosnaeni; Hamdat, Aminuddin; Rizal, Muhammad; Dewi B, Ceskakusuma; Lawalata, Izaac L D; Fauziah, Fauziah (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
This activity aims to build core competencies to address juvenile delinquency in schools through a strategic management approach. The method used was a material presentation combined with interactive discussions involving the village head, religious leaders, community elders, housewives, and youth figures. Internal school environment analysis was conducted to identify tangible assets, intangible assets, and organizational capabilities supporting delinquency prevention. Demographic data revealed that the 10–24 age group holds the highest potential for juvenile delinquency in Kassiloe Village. Addressing this issue requires synergy between family, community, and school environments. Schools must develop core competencies by enhancing infrastructure, building a good reputation, and strengthening management capabilities. The program was held on November 6, 2024, with active participation and discussions. The parent-student-teacher interaction model was also emphasized to strengthen collaboration in fostering youth character development.